Eksistensi Hukum Adat di Era Modernisasi - Achmad Asfi Burhanudin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
Customary law is the values ​​that live and develop in the community of a region. Although most customary law is unwritten, it has a strong binding force in society. In fact, customary law is still needed in responding to the complexity of the vortex of globalization. Customary law is the values ​​(truth and justice) that live in society. and applies in the community (living live), namely customary law is made part of national law. This affirmation relates to the inclusion of two new articles in the second amendment to the 1945 Constitution, namely Article 18 B Paragraph (2) which states that the state recognizes and respects customary law community units and their traditional rights as long as they are still alive and in accordance with community development and principles. The Unitary State of the Republic of Indonesia as regulated by law. Next, Article 28 1 Paragraph (3) which states that the cultural identity and rights of traditional communities are respected in line with the development of the times and civilization. The existence of customary law as a form of law that is recognized for its existence in the life and legal culture of the Indonesian people is stated in the 1945 Constitution of the Republic of Indonesia or for short the 1945 Constitution, namely in Article 18B paragraph (2) which stipulates “The State recognizes and respects the unity of the people of Indonesia.